Blood-Flow–Restricted Strength Training Combined With High-Load Strength and Endurance Training in Pulmonary Rehabilitation for COPD: A Case Report. Issue 6 (14th February 2021) - Kohlbrenner, Dario; Aregger, Céline; Osswald, Martin; Sievi, Noriane A; Clarenbach, Christian F
Abstract: Objective: The purpose of this report is to describe the case of a patient with chronic obstructive pulmonary disease (COPD) who was load compromised and being referred for outpatient pulmonary rehabilitation. Low-load blood flow restriction strength training (LL-BFRT) was applied to prepare for and increase tolerability of subsequently applied high-load strength training. Methods (Case Description): A 62-year-old woman with COPD GOLD 2 B presented with severe breathlessness. Lower limb strength was severely reduced while functional exercise capacity was preserved. The patient was severely load compromised and had high risk to be intolerant of the high training loads required to trigger the desired adaptations. LL-BFRT was applied during the first 12 training sessions and high-load strength training in the subsequent 12 training sessions of the rehabilitation program. Endurance training on a cycle ergometer was performed throughout the program. Results: Symptom burden in the COPD assessment test was reduced by 6 points (40%). Lower limb strength improved by 95.3 Nm (521%) and 88.4 Nm (433%) for the knee extensors and by 33.8 Nm (95%) and 56 Nm (184%) for the knee flexors, respectively. Functional exercise capacity improved by 44 m (11%) in the 6-minute walk test and 14 repetitions (108%) in the 1-minute sit-to stand test. The patient did not experience any adverse events related to the exercise training. Conclusion: Clinically relevant changes were observed in both strength-related functional and self-reported outcomes. The achievements translated well into daily living and enabled functioning according to the patients' desires. LL-BFRT was reported to be well tolerated and implementable into an outpatient pulmonary rehabilitation program. Impact: The description of this case encourages the systematic investigation of LL-BFRT in COPD. LL-BFRT has the potential to increase benefits as well as tolerability of strength training in pulmonary rehabilitation. Consideration of the physiological changes achieved through LL-BFRT highlights potential in targeting peripheral muscle dysfunction in COPD.